1993
DOI: 10.1073/pnas.90.15.7024
|View full text |Cite
|
Sign up to set email alerts
|

Regression of established macroscopic liver metastases after in situ transduction of a suicide gene.

Abstract: The In some animals, the residual tumors were devoid ofcancer cells.This treatment efficacy appears in part due to a "bystander effect" in which phosphorylated ganciclovir could be transferred from cell to cell and to an active local immune reaction evidenced by massive infiltration of the tumors by macrophages and both CD4+ and CD8+ lymphocytes. This efficient therapeutic approach might be an ultimate treatment for disseminated liver metass in hums and could also be applied to treatment of a large variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
167
2
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(173 citation statements)
references
References 18 publications
3
167
2
1
Order By: Relevance
“…This agrees with findings in studies in which antitumour immunity has been induced and where these two cell types have been found to be of importance (Caruso et al, 1993;Barba et al, 1994;Consalvo et al, 1995;Yamamoto et al, 1997;Xiang et al, 1998;Kuriyama et al, 1999a, b). Antitumour immunity is a complex phenomenon.…”
Section: Discussionsupporting
confidence: 89%
“…This agrees with findings in studies in which antitumour immunity has been induced and where these two cell types have been found to be of importance (Caruso et al, 1993;Barba et al, 1994;Consalvo et al, 1995;Yamamoto et al, 1997;Xiang et al, 1998;Kuriyama et al, 1999a, b). Antitumour immunity is a complex phenomenon.…”
Section: Discussionsupporting
confidence: 89%
“…Even 22 weeks after the end of the treatment, no tumor recurrence was detectable. Although some studies showed that at the doses needed to eliminate the tumor, GCV causes leukopenia, diarrhea, 508 and some treatment-related mortality, 51 in our experiments GCV treatment did not cause such symptoms in the animals. Also, we did not observe weight loss during GCV therapy.…”
Section: Discussioncontrasting
confidence: 67%
“…21 Several studies have suggested the contribution of immunologic mechanisms in mediating the bystanderkilling effects in colon cancer cells. 22,23 We hypothesized that the bystander effect could be enhanced by inducing immunogenicity against the tumor. The GM-CSF gene was used because it is known to encode for a cytokine that is highly potent in inducing antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%